2002
DOI: 10.2337/diabetes.51.8.2395
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Rate of Muscle Proteins, Muscle Functions, and Amino Acid Kinetics in Type 2 Diabetes

Abstract: Improvement of glycemic status by insulin is associated with profound changes in amino acid metabolism in type 1 diabetes. In contrast, a dissociation of insulin effect on glucose and amino acid metabolism has been reported in type 2 diabetes. Type 2 diabetic patients are reported to have reduced muscle oxidative enzymes and VO 2max . We investigated the effect of 11 days of intensive insulin treatment (T 2 D؉) on whole-body amino acid kinetics, muscle protein synthesis rates, and muscle functions in eight typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 64 publications
10
111
2
1
Order By: Relevance
“…However, in response to long-term intensive s.c. insulin treatment, Halvatsiotis et al found no difference in mitochondrial, sarcoplasmic or mixed MPS compared with healthy controls who did not receive insulin [50]. Whether increased AA intake in insulin-treated patients with diabetes will lead to increased muscle mass is not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, in response to long-term intensive s.c. insulin treatment, Halvatsiotis et al found no difference in mitochondrial, sarcoplasmic or mixed MPS compared with healthy controls who did not receive insulin [50]. Whether increased AA intake in insulin-treated patients with diabetes will lead to increased muscle mass is not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the muscle specimens obtained from amputated limbs in that study (34) were from patients under suboptimal glucose control and͞or with peripheral vascular disease. Recent studies performed in people with type 2 DM demonstrated that 2 wk of insulin treatment did not stimulate COX activity and mitochondrial protein synthesis (12).…”
Section: Discussionmentioning
confidence: 99%
“…At 0400 hours of each inpatient period, a priming dose of L-[1,2-13 C]leucine (1.8 mg͞kg of FFM) was administered through a peripheral forearm vein. This was followed by a continuous infusion of L- [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]leucine (1.8 mg͞kg of FFM per h). Insulin [1.5 milliunits (mU)͞kg of FFM per min] or normal saline infusion was randomized and began at 0700 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is associated with the occurrence of well described microvascular complications that affect different organs, leading most commonly to retinopathy, nephropathy and peripheral neuropathy, the development of which is dependent on the duration of the disease and glycaemia control [17]. the term -diabetic encephalopathy‖ was introduced in 1950 to describe the complication of diabetes resulting on brain dysfunction and leading to cognitive impairment.…”
Section: Urea Cyclementioning
confidence: 99%